Genome-Wide Tool for Sensitive de novo Identification and Visualisation of Interspersed and Tandem Repeats - Ruslan Kalendar; Ulykbek Kairov (Bioinformatics and Biology Insights, 2024)
Genomic repeats are functionally ubiquitous structural units found in all genomes. Studying these repeats of different origins is essential for understanding the evolution and adaptation of a given organism. These repeating patterns have manifold signatures and structures with varying degrees of homology, making their identification challenging. To address this challenge, we developed a new algorithm and software that can rapidly and accurately detect any repeated sequences de novo with varying degrees of homology in genomic sequences in interspersed or clustered repeats. Numerous forms of repeated sequences and complex patterns can be identified, even for complex sequence variants and implicit or mixed types of repeat blocks. Direct and inverted-repeat elements, perfect and imperfect microsatellite repeats, and any short or long tandem repeat belonging to a wide range of higher-order repeat structures of telomeres or large satellite sequences can be detected. By combining precision and versatility, our tool contributes significantly to elucidating the intricate landscape of genomic repeats.